Identification of Factors that Prevent Park and Recreation Area Users from Participating in Physical Activity and Choosing a Place: The Example of Düzce - Filiz SÜLEYMANOĞLU; Levent ATALI (ümit doğan üstün, 2023)
The purpose of this study was to identify the factors that prevent park and recreation area users in Düzce from engaging in physical activity and the factors that inhibit their choice of location. While the population of this study consisted of park and recreation area visitors over the age of 15 in Düzce, the sample group consisted of 290 individuals selected using the method of convenience sampling. To collect data "Physical activity space rating scale (FAMDO)" (Gümüş et al., 2015) was used. The scale has two subdimensions and thirty-three items. The first sub-dimension of the scale is comprised of factors that influence the selection of a physical activity venue, and the second sub-dimension is comprised of factors that inhibit the frequency of physical activity participation. The scale, which was preperad in a computer environment, was distributed online via Google forms to the participants. After determining that the data were reliable, a normality analysis was performed to determine which analyses would be applied to the data. On the basis of the results of analyses of reliability and normality, descriptive statistics were conducted first. Using the Independent Sample T test and ANOVA, the differences between the variables were examined. Consequently, when the participants' preferences for visiting these areas were examined, "spending time," "sitting / resting," and "psychological relaxation" ranked first, second, and third, respectively. Examining the results of the analysis reveals that there is a difference between high school, undergraduate, and graduate graduates and primary school graduates on both subdimensions. Furthermore, it has been determined that single people prefer these areas more than married people. According to the findings of the study, individuals with chronic diseases prefer these areas less than those without chronic diseases.